Nicaragua : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
This paper is an overview of Nicaragua's performance in the year 2011. The year 2012 is expected to face a recession and a moderation in the global oil prices. The tax revenue collections will be sturdy. The poverty scale will not face any oscillation. The rigid development in the business line, sustaining the electricity sector financially, and low dependence of oil imports are the anticipated preventive measures to overcome these challenges. The Board has taken these ideas as the positive outcome of a strong rule.